Generation of three induced pluripotent stem cell lines from hypertrophic cardiomyopathy patients carrying TNNI3 mutations - Shane Rui Zhao (Elsevier, 2021)
Hypertrophic cardiomyopathy (HCM) is a common inherited heart disease with a prevalence of about 0.2%. HCM is typically caused by mutations in genes encoding sarcomere or sarcomere-associated proteins. Here, we characterized induced pluripotent stem cell (iPSC) lines generated from the peripheral blood mononuclear cells of three HCM patients each carrying c.433C > T, c.610C > T, or c.235C > T mutation in the TNNI3 gene by non-integrated Sendai virus. All of the three lines exhibited normal morphology, expression of pluripotent markers, stable karyotype, and the potential of trilineage differentiation. The cardiomyocytes differentiated from these iPSC lines can serve as useful tools to model HCM in vitro.